Genetic and Genomic Public Health Strategies: Imperatives for Neonatal Nursing Genetic Competency - Williams, Pamela S Holtzclaw (2002)
Genetics and genomics are emerging as the central science for 21(st) century health care. Proficient nursing care incorporates this central science. Nursing genetic competency includes anticipating future demands spurred by knowledge advancement. Three emerging public health areas that call for future neonatal nursing genetic competency development will be discussed here: increasing emphasis on neonatal family health histories, population genetic biobanking, and family genetic advocacy. Neonatal nurses can develop genetic competency by targeting: 1) Collaborative efforts between nurse and family regarding neonatal family health history preparation and understanding its genetic implications; 2) Referrals to and partnerships with genetic advocacy groups in programs that empower neonate's families; 3) Familiarity with biobank practices that interface nursing care domains.